2015
DOI: 10.18632/oncotarget.5479
|View full text |Cite
|
Sign up to set email alerts
|

Adiponectin promotes VEGF-A-dependent angiogenesis in human chondrosarcoma through PI3K, Akt, mTOR, and HIF-α pathway

Abstract: Chondrosarcoma is a type of highly malignant tumor with a potent capacity to invade locally and cause distant metastasis. Adiponectin is a protein hormone secreted predominantly by differentiated adipocytes. On the other hand, angiogenesis is a critical step in tumor growth and metastasis. However, the relationship of adiponectin with vascular endothelial growth factor-A (VEGF-A) expression and angiogenesis in human chondrosarcoma is mostly unknown. In this study we first demonstrated that the expression of ad… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
43
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
3

Relationship

1
9

Authors

Journals

citations
Cited by 79 publications
(52 citation statements)
references
References 48 publications
(58 reference statements)
3
43
1
Order By: Relevance
“…As a potent proangiogenic factor, VEGF is involved in the development of several ophthalmic diseases in humans, such as diabetic retinopathy age-related macular degeneration and retinopathy of prematurity, and HIF-1α is a major upstream regulator of VEGF [41]. The role of mTOR in the regulation of HIF-1α-mediated VEGF expression has been previously documented [42, 43]. In our results, loss of Deptor resulted in activation of mTORC1 signaling in vascular ECs and subsequently contributed to the promotion of angiogenesis through up regulation of HIF-1α and VEGF expression.…”
Section: Discussionmentioning
confidence: 99%
“…As a potent proangiogenic factor, VEGF is involved in the development of several ophthalmic diseases in humans, such as diabetic retinopathy age-related macular degeneration and retinopathy of prematurity, and HIF-1α is a major upstream regulator of VEGF [41]. The role of mTOR in the regulation of HIF-1α-mediated VEGF expression has been previously documented [42, 43]. In our results, loss of Deptor resulted in activation of mTORC1 signaling in vascular ECs and subsequently contributed to the promotion of angiogenesis through up regulation of HIF-1α and VEGF expression.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, serum adiponectin in patients with gastric cancer has been found to inversely correlate with pathological findings such as tumour size, depth of invasion and tumour stage [32]. In chondrosarcoma, we previous reported that adiponectin increases integrin α 2 β 1 [33] and VEGF-A expression [34], as well as subsequently promoting migration and angiogenesis; this implies that adiponectin is involved in a metastatic process of chondrosarcoma. However, it is still not well recognized whether adiponectin increases VEGF-C expression to facilitate tumourassociated lymphangiogenesis in human chondrosarcoma.…”
Section: Introductionmentioning
confidence: 94%
“…Bcl-2 gene expression is regulated by activation of Akt [121] and Akt influences regulation of VEGF-A expression [162]. VEGF-A expression is promoted by ADI-POQ through the ADIPOQ receptor, AdipoR [163]. ADIPOQ and OBS are able to induce VCAM-1 expression [164].…”
Section: Apoptosis In Asthma/hypertension Gene Networkmentioning
confidence: 99%